Pengaruh Strategi Diversifikasi Terhadap Nilai Perusahaan Lq-45 Pada Bursa Efek Indonesia - Dianita Asih Lestari (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2015)
AbstractStock price volatility in 2013 make the Indonesian economy slumped. It is due to the decrease in the ability of the company to get profitability, especially the listed LQ 45. The strategy diversification that undertaken by all companies LQ 45 is not quite significant to bring the company to not be affected as a result of the stock crisis. The firm value has also become an important thing to consider in the stock crisis because the firm value will show how much advantage to be gained by stockholders. Diversification strategy expected to increasefirm value. Research Muliani, dkk, 2014 showed positive relationship between firm value and performance of the company. While Harto, 2006 showed that the strategy of diversification not have an optimal effect on the performance of the company.The study was conducted by purposive sampling method with 33 samples of LQ 45 companiesin 2013. The data processing using SPSS 20 with a simple regression analysis. Results of this study show a diversification strategy has no significant effect towardsfirm value.